BSI Digital Financial Transition Mechanism in Improving the Financial Literacy of Urban and Rural Communities in Majene - Rahmawati Rahmawati; Syahriyah Semaun (Journal of Economics and Social Sciences (JESS), 2026)
The transformation of digital finance in the Islamic banking sector has become inevitable due to rapid technological progress and rising demand for inclusive efficient services. This study examines the digital transition mechanism implemented by Bank Syariah Indonesia in enhancing financial literacy in urban and rural communities of Majene Regency. Using a qualitative case study approach, data were collected through interviews, observations, and documentation involving bank staff, customers, MSMEs, and community leaders. Thematic interactive analysis reveals that digital banking, especially mobile applications, functions as an informal learning medium that gradually improves financial literacy. Urban users benefit more due to better infrastructure and digital skills, while rural communities face barriers including limited access, low technological understanding, and trust issues. Religiosity and adherence to sharia principles also shape adoption decisions. Thus, literacy is influenced not only by knowledge and skills but also by social norms and beliefs. Overall, digital financial transformation represents a multidimensional social process requiring integrated innovation, community engagement, and supportive infrastructure to ensure inclusive and sustainable outcomes. Future strategies should emphasize localized education, user experience adaptation, and trust building initiatives to bridge the urban rural divide and maximize the impact of Islamic digital finance development across diverse community settings effectively.